GAMBARAN KONDUKSI SARAF TEPI NEUROPATI ASIMPTOMATIK PADA PENYAKIT GINJAL KRONIS STADIUM 3 DAN 4 4 - Tania Sananta (NEURONA, 2022)
Introduction Neuropathy is the most common neurologic complication in Chronic Kidney Disease (CKD) patients. Uremic neuropathy usually happen when glomerular filtration rate fall below 12 mL/minute (stage 5), but factors contributing development of uremic neuropathy actually can be found in earlier stage of CKD. Previously the nerve conduction studies in asymptomatic neuropathy CKD stage 3 and 4 patients is not known. Aim To identify nerve conduction studies in asymptomatic neuropathy CKD stage 3 and 4 patients Methods This was a cross sectional, observational descriptive study conducted in patients with stage 3 and 4 CKD without symptoms and sign of neuropathy. The study was done in two hospital in Bandung from December 2017 until March 2018. Nerve conduction study was done in eligible subjects. Results There were 16 subjects, age 22–72 (81% men, 19% women) with glomerular filtration rate 32,2±11,6ml/minute. Nerve conduction study showed that 37,5% subject had asymptomatic neuropathy. The most common type were axonal sensory motor polyneuropathy with lower extremities predominance. Stage 4 CKD patients have 57,14% prevalence of neuropathy and stage 3 CKD patients have 22,22%. Discussion Nerve conduction study showed axonal damage ini sensoric and motoric fibers with predominance in the longest axon and the farthest axon from cell body. Neuropathy was more frequent in later stage of CKD. One third of stage 3 and 4 CKD patients had polyneuropathy even without clinical symptoms of neuropathy. . Keywords : Asymptomatic neuropathy, stage 3 and 4 chronic kidney disease